KINERJA KARYAWAN DITINJAU DARI GAYA KEPEMIMPINAN TRANSFORMASIONAL, PENGEMBANGAN KARIR DAN KOMUNIKASI (Studi Kasus Pada Karyawan BPJS Ketenagakerjaan Surakarta) - Bagus Kuncoro Adi; Bambang Mursito; Sarsono Sarsono (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
The purpose of this study was to determine the effect of transformational leadership style, career development and communication on the performance of employees of Surakarta Employment BPJS. This type of research is a quantitative research. The population in this study included all BPJS Ketenagakerjaan employees, totaling 40 people. The sample technique taken is saturated sample technique, so the number of samples in this study amounted to 40 people. Based on the results of the t test it is concluded that transformational leadership style has a positive effect on the performance of BPJS Ketenagakerjaan employees in Surakarta, career development has a positive effect on the performance of BPJS Ketenagakerjaan employees in Surakarta and communication has no positive effect on the performance of BPJS Ketenagakerjaan employees in Surakarta.